Sistema web para la administración, control y seguimiento de proyectos arquitectónicos. - Jiménez Jiménez, Ramiro Josimar, Daniel Emilio León Ortega (2016)
The following Degree Work with title is “ARCHITECTURAL PROJECT MONITORING SYSTEM FOR WEB MANAGEMENT, CONTROL AND DEVELOPED FOR THE COMPANY ARQUINOVA”, it has like an objective to guarantee the management, control and monitoring applied to projects that company. The system allows entry of users, projects, materials used, staff responsible for carrying the control and monitoring of each project, entering tasks, view the status of each of the tasks the project. Also, every project has to comply iterations, stories of the completion of each iteration, tasks assigned to each team, statistical detail the progress of each project and overall summary. The system has a module for the administrator, which will allow for the appropriate management, control and detailed monitoring of the projects is in charge at your company. The IEEE 830 standard is used to determine the software requirements - 1998, as development tools XAMPP is a package consisting of Apache, with motor MYSQL database and PHP language interpreter, the framework used Laravel 4.0 which it is completely based on the MVC (Model - View - Controller) design. It is important to clarify that the system has been developed with the bootstrap component, following the guidelines proposed by this tool adaptable model of web design, which allow the user to have a pleasant experience with the system in any device.